UPAYA PENCEGAHAN STUNTING DENGAN HIGIENE INDIVIDU DAN KEAMANAN PANGAN DI DESA LEBIH GIANYAR - Dwipayanti, N.M.U.; Indrayathi, P.A.; Kurniawati, D.P.Y.; Adhi, K.T. (Buletin Udayana Mengabdi, 2024)
One of the health priorities in the Sustainable Development Goals is address malnutrition, including stunting among children. Gianyar Regency is one of the districts with the highest prevalence of stunting. Previous studies showed that the incidence of stunting in the locus area was due to lack of hygienic behavior in food handling for infant and the availability of safe drinking water, thus this behaviour need intervention. The intervention targeted mothers of children under five and pregnant women in posyandu (a community based health care). The activity integrates the nutritional emodemo approach and Community-Based Total Sanitation, pillar 2 and pillar 3. This intervention aimed to empower village cadres and the community to take collective action for behavior change and independently maintain the sustainability of these changes. Trained posyandu cadres carry out promotional activities at the posyandu. Posyandu participants in Bajar Kesian, Lebih Duur Kaja and Lebih Beten Kelod were provided with health promotions related to healthy nutrition, personal hygiene and safety of food and household drinking water. This promotional activity is expected to be carried out regularly by posyandu cadres in their respective posyandu, thus it will become a continuous promotion effort in Lebih Village to improve healthy and hygienic parenting. Keywords: cadres, Gianyar, food hygiene, personal hygiene, posyandu, stunting